Experimental analysis of reinforced concrete block masonry walls subjected to in-plane cyclic loading - Haach, Vladimir G. (2010)
An innovative system for reinforced concrete masonry walls based on the combination of vertical and horizontal trussed reinforcement is proposed. The mechanical characterization of the seismic behavior of such reinforced masonry walls is based on static cyclic tests carried out on panels with appropriate geometry. The influence of the factors influencing the in-plane cyclic behavior of concrete masonry walls, such as the horizontal reinforcement, precompression, and masonry bond pattern, is discussed. The results are analyzed in terms of failure modes and force versus displacement diagrams, from which the seismic performance is assessed based on the ductility and energy capacity dissipation. The results stressed that the increase on the precompression level leads to a stiffer and more brittle lateral behavior of the masonry walls. The presence of horizontal reinforcement ensures better control and better distribution of cracking, even if only a marginal increase of lateral strength was found in the particular testing program.